Neuroprotective effects of intraperitoneally injected Mg alloy extracts on middle cerebral artery occluded mouse with reperfusion injury - Lanjing Wang; Yue Hu; Hongkang Zhang; Miaowen Jiang; Yang Zhang; Yumin Luo; Xunming Ji; Yufeng Zheng; Sijie Li; Ming Li (Journal of Magnesium and Alloys)
Magnesium (Mg) alloy stents have been commercialized for the treatment of cardiovascular diseases and extensively studied for possible implantation in major organs. However, the in vivo studies regarding the neuroactivity of Mg alloys extracts are few. Therefore, the safety and neuroprotective effects of released degradation products (Mg2+ and H2) from Mg alloys on ischemic brain tissues were investigated. To be specific, C57BL/6 mice with middle cerebral artery occlusion (MCAO) were injected intraperitoneally of saline, pure Mg extracts, WE43 extracts and hydrogen (H2)-removed WE43 Mg alloy extracts (75 mL/kg) respectively immediately after reperfusion. The neurobehavioral assessment stated clearly that WE43 extracts could remarkably recover the neurological deficits of MCAO mice. We explored the underlying mechanisms and demonstrated that the Mg2+ and H2 from WE43 extracts could perform anti-inflammatory and anti-oxidative function after MCAO in mice, by increasing the expressions of IL-4, TGF-β1, SOD1 and decreasing the expressions of IL-1β, CXCR2, MDA. Simultaneously, Mg2+ and H2 contributed to increase cerebral blood flow and restore blood-brain barrier integrity. In conclusion, this study provides certain theoretical representation of the application of Mg alloy stents in intracranial vessels.